Factors Influencing Background Parenchymal Enhancement in Breast Contrast-Enhanced Mammography: A Retrospective Study - Xue J; Qu T; Li Z; Shi B; Yang G; Rong X; Li Y; Lin G; Ping Y (International Journal of Women's Health)
Jing Xue,1 Tianyun Qu,1 Zhigang Li,1 Bo Shi,1 Guang Yang,1 Xiaocui Rong,1 Yazhou Li,1 Guoquan Lin,2 Yong Ping1 1Department of Radiology; Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People’s Republic of China; 2Department of General Surgery; Botou Hospital, Cangzhou City, Hebei Province, 062150, People’s Republic of ChinaCorrespondence: Yong Ping, Email Ulrica150sci@163.comObjective: To evaluate the association between background parenchymal enhancement (BPE) level and extent on contrast-enhanced mammography (CEM) with age, menopausal status, breast density, and menstrual cycle phase in women. Additionally, to characterize the dynamic changes in BPE during CEM.Methods: This retrospective study included 103 women who underwent CEM at a single institution between September 2019 and November 2021 for screening or diagnostic purposes. Menopausal status and menstrual cycle phase were recorded for all patients. BPE on subtracted CEM images was assessed quantitatively (region of interest [ROI] analysis of pixel values) and qualitatively (subjective classification). Statistical analysis was performed to determine the relationship between BPE (level and extent) and age, menopausal status, breast density, and menstrual cycle phase. Dynamic changes in BPE level over time were also analyzed.Results: Both BPE level and extent were negatively correlated with age (P=0.004, r=− 0.280; P=0.001, r=− 0.318). Postmenopausal women exhibited lower BPE level and extent compared to premenopausal women (P=0.003, Z=− 2.958; P=0.042, 2=4.123). No significant association was observed between BPE and breast density or menstrual cycle phase (P> 0.05). BPE level increased significantly from 3 to 9 minutes post-contrast injection (P< 0.001, t=− 10.7).Conclusion: BPE in CEM is significantly associated with age and menopausal status. Further research is needed to clarify the relationship between BPE and breast density and menstrual cycle phase. BPE demonstrates a dynamic increase in level over time, this relates to post-contrast injection, rather than to the age of the woman.Keywords: Mammography, Breast, Female Patients